Quality of Hadith Shalih in the Book of Sunan Abiy Dâwud Disputed by Nasr al-Dîn al-Albâniy and Shu'aib al-Arnauth - Afdilla Nisa (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
This study intends to examine the quality of hadîth shalih in the book Sunan Abiy Dâwud which was disputed by Nâshir al-Dîn al-Albâniy and Syu'aib al-Arnauth, namely by using library research (library research), which is to collect accurate and relevant data. This is then processed with a descriptive qualitative analytical approach through inductive and comparative thinking methods. In addition, it also uses the hadîth research step to determine the quality of hadîth both from the side of the sanad and its eyes. Based on the analysis, it can be concluded that the hadiths termed shahih Abû Dâwud, which are also debated by al-Albaniy and al-Arnauth in assessing their quality, when tested with authentic criteria do not necessarily mean maqbûl or authentic quality. and hasan, but some have the status of dha'if. Thus hadîth shalih can contain two possibilities, namely lil i'tibâr (to be studied) or li al-ihtijâj (used as evidence). Penelitian ini bermaksud mengkaji kualitas hadîth shalih dalam kitab Sunan Abiy Dâwud yang diperselisihkan oleh Nâshir al-Dîn al-Albâniy dan Syu’aib al-Arnauth, yaitu dengan menggunakan library research (penelitian kepustakaan) yaitu mengumpulkan data-data yang akurat dan relevan dengan pembahasan ini kemudian diolah dengan metode pendekatan deskriptif analitis kualitatif melalui metode berfikir induktif dan komparatif. Di samping itu penulis juga menggunakan langkah penelitian hadis untuk mengetahui kualitas hadis baik dari sisi sanad maupun matan-nya. Berdasarkan analisa dapat disimpulkan bahwa hadis yang diistilahkan shâlih Abû Dâwud, yang juga diperdebatkan al-Albâniy dan al-Arnauth dalam menilai kualitasnya, ketika diuji dengan kriteria ke-shahih-an tidak serta merta berarti maqbûl atau berkualitas shahih dan hasan, akan tetapi ada yang berstatus dha’if. Dengan demikian hadîth shalih dapat mengandung dua kemungkinan yaitu lil i’tibâr (untuk dikaji) atau li al-ihtijâj (dijadikan hujjah).